1992
DOI: 10.2307/1940755
|View full text |Cite
|
Sign up to set email alerts
|

Density‐Dependent Host‐Pathogen Dynamics in Soil Microcosms

Abstract: Temporal density—dependent parasitism and a host threshold density are important features of disease induced by infectious parasites in populations of aboveground, macroscopic organisms. We determined whether these features also occur in soil microcosms containing a microscopic host (the nematode Heterodera schachtii) and its parasite (the nematophagous fungus Hirsutella rhossiliensis). Soil microcosms are especially interesting because (1) the environment and scale are quite different from conventional host—p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(36 citation statements)
references
References 19 publications
1
33
0
Order By: Relevance
“…This raises the question whether the parasitism of nematophagous fungi can regulate the population size of soil nematodes. Experiments in soil microcosms using the endoparasitic fungus H. rhossoliensis and plant parasitic nematodes have shown that the level of fungal parasitism is dependent on the nematode density, although there is a relatively long time lag in the response of the fungal population to changes in the number of nematodes (Jaffee et al, 1992). See also: Parasitism: the variety of parasites Mostly, plant-parasitic nematodes attack plant roots and, therefore, the ability of the nematophagous fungi to grow in the rhizosphere is of great importance for their capacity to control these nematodes.…”
Section: Ecology Of Nematophagous Fungimentioning
confidence: 99%
“…This raises the question whether the parasitism of nematophagous fungi can regulate the population size of soil nematodes. Experiments in soil microcosms using the endoparasitic fungus H. rhossoliensis and plant parasitic nematodes have shown that the level of fungal parasitism is dependent on the nematode density, although there is a relatively long time lag in the response of the fungal population to changes in the number of nematodes (Jaffee et al, 1992). See also: Parasitism: the variety of parasites Mostly, plant-parasitic nematodes attack plant roots and, therefore, the ability of the nematophagous fungi to grow in the rhizosphere is of great importance for their capacity to control these nematodes.…”
Section: Ecology Of Nematophagous Fungimentioning
confidence: 99%
“…For free-living propagules, density dependence arises because the probability of transmission is a function of parasite density and parasite density is a function of past host density (e.g. Jaffee et al, 1992). Host density seems clear enough for nematodes, bacteria and insects, but variable size and morphology complicate the definition of what comprises an individual fungus; for fungi, the term biomass-dependent parasitism might be more appropriate than density-dependent parasitism (Cook & Baker, 1983).…”
Section: Density-dependent Transmissionmentioning
confidence: 99%
“…Although the effect of the environment on the transmission dynamics of gastrointestinal parasites is evident (Haufstater and Meade 1982;Jaffee et al 1992;Roepstorff and Murrell 1997;Slifko et al 2000;Patz et al 2000), many studies compare host populations that differ drastically in only one important environmental component (i.e. water availability or habitat) (Anderson and Beaudoin 1966;Grutter 1998;Baird 2003;Ferrari et al 2004;TrejoMacias et al 2007).…”
Section: Introductionmentioning
confidence: 99%